PENGARUH METODE STORYTELLING BERBANTUAN VIDEO TERHADAP KETERAMPILAN MENYIMAK DAN BERBICARA SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI 064025 TJ. SELAMAT MEDAN TAHUN PEMBELAJARAN 2025/2026 - Citra Br. Siagian; Reflina Sinaga; Joen Parningotan Purba; Juliana Panjaitan; Heka Maya Sari Br. Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of applying the storytelling method assisted by video media on the listening and speaking skills of fifth-grade students in Indonesian subjects at SD Negeri 064025 Tj. Selamat Medan in the 2025/2026 Academic Year. This type of research is quantitative with an experimental approach using a re-Experimental Design in the form of a One Group Pretest-Posttest Design. The research sample consisted of 24 students of class VD taken using a Purposive Sampling technique. Data collection techniques used tests, observation, questionnaires, and documentation. The results showed that students' listening skills before being given treatment (pretest) obtained an average score of 60.62 and speaking skills of 56. After being treated by applying the storytelling method assisted by video media, the posttest average score for listening skills increased to 80.83 and speaking skills to 80.66. Based on the hypothesis testing (t-test), the value of t count≥ t table is 2.508 ≥ 2.047, which means that there is a significant influence of using the storytelling method assisted by video media on the listening and speaking skills of fifth-grade students.